Development of the augmented reality app for forestry application: ForestAR - S. K. P. Kushwaha; A. Rai; H. Hristova; A. Sagar; M. Mokros; J. Schweier (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Augmented Reality (AR) is being widely applied across various fields, seamlessly integrating with real-world scenarios. In forestry, there is significant potential for the use of AR to improve our understanding of the datasets along with the physical environment of the surroundings. Remote Sensing is a powerful technology that generates highly accurate datasets, with Light Detection and Ranging (LiDAR) Remote Sensing technology being particularly effective in creating geometrically precise point cloud datasets. By integrating LiDAR datasets with AR applications, we can unlock numerous benefits. For one, the development of AR technologies in forestry can significantly improve the visualization, monitoring, management, and education of forest ecosystems by providing immersive digital experiences. This paper aims to demonstrate the potential of an AR application for visualizing different configurations of Terrestrial Laser Scanners (TLS) and Classified Point Cloud (CPC) of a forest plot. Such an AR approach offers a unique way to comprehensively examine forest structures. It also allows for the effective recreation, visualization, and presentation of an interactive environment of forest areas.